Self-transcendent leadership: A meta-perspective - Maximilian H. Theissen; Hubertus H. Theissen; Ali A. Gümüsay (European Management Review, 2024)
Self-transcendence as a concept is increasingly found in leadership literature—yet in diverse ways. It is this diversity that serves as the motivation for the current article in which we develop a comprehensive and coherent conceptualization of self-transcendence for leadership research. We demonstrate that self-transcendence is the cognitive orientation of accepting something other than one's self to be of highest worth. We show that this something, which is greater than the self, may take four different forms: other people, social collectives, moral principles and ideals, or metaphysical beings. We contribute to leadership research by linking each greater something to one theory: servant, transformational, moral, and spiritual leadership. Our conceptualization of self-transcendence allows us to integrate different leadership theories into a meta-perspective of self-transcendent leadership. We conclude with implications for leadership research as well as practice.
Keywords: 650; leadership ethics; leadership theory; self-interest; self-transcendence